2022
DOI: 10.3201/eid2807.212505
|View full text |Cite
|
Sign up to set email alerts
|

Determining Infected Aortic Aneurysm Treatment Using Focused Detection of Helicobacter cinaedi

Abstract: We detected Helicobacter cinaedi in 4 of 10 patients with infected aortic aneurysms diagnosed using blood or tissue culture in Aichi, Japan, during September 2017-January 2021. Infected aortic aneurysms caused by H. cinaedi had a higher detection rate and better results after treatment than previously reported, without recurrent infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Later, the bacterium was found in other patient groups, including women and children ( Vandamme et al, 1990 ; Skirrow et al, 1993 ). Currently, both cases of H. cinaedi infection against a background of immunodeficiencies ( Saito et al, 2022 ; Roupie et al, 2023 ) and in immunocompetent patients have been reported ( Akiyama et al, 2021 ; Toyoshima et al, 2022 ).…”
Section: Pathologies Associated With the Bacterium Helicoba...mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the bacterium was found in other patient groups, including women and children ( Vandamme et al, 1990 ; Skirrow et al, 1993 ). Currently, both cases of H. cinaedi infection against a background of immunodeficiencies ( Saito et al, 2022 ; Roupie et al, 2023 ) and in immunocompetent patients have been reported ( Akiyama et al, 2021 ; Toyoshima et al, 2022 ).…”
Section: Pathologies Associated With the Bacterium Helicoba...mentioning
confidence: 99%
“…This is the first project of a preventive strategy whose action is directed specifically at this microorganism. Today, treatment of patients infected with H. cinaedi is based on antibiotic therapy ( Lenskaya et al, 2022 ; Saito et al, 2022 ; Roupie et al, 2023 ).…”
Section: Pathologies Associated With the Bacterium Helicoba...mentioning
confidence: 99%
“…Helicobacter cinaedi is the most frequently isolated enterohepatic Helicobacter species strain from humans, mainly found in immunocompromised patients with bacteremia. H. cinaedi is responsible for recurrent cellulitis, infected aortic aneurysm, subdural hematoma, and hepatic cyst infection ( 2 6 ). H. cinaedi was first isolated in 1984 from a homosexual man with intestinal symptoms in Seattle, and it was first isolated in Japan in 2003 ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…H. cinaedi is the most frequently isolated enterohepatic Helicobacter species strain from humans, mainly found in immunocompromised patients with bacteremia. H. cinaedi is responsible for recurrent cellulitis, infected aortic aneurysm, subdural hematoma, and hepatic cyst infection (2)(3)(4)(5)(6). H. cinaedi was first isolated in 1984 from a homosexual man with intestinal symptoms in Seattle and it was first isolated in Japan in 2003 (7,8).…”
Section: Introductionmentioning
confidence: 99%